PENERAPAN PROXY SERVER BERBASIS CLEAROS 7 UNTUK MANAJEMEN AKSES PADA INTERNET: PENERAPAN PROXY SERVER BERBASIS CLEAROS 7 UNTUK MANAJEMEN AKSES PADA INTERNET - I Putu Agus Eka Pratama; I Putu Gede Eka Yuda Arista (Institute of Computer Science (IOCS), 2019)
The development of technology, especially information technology has developed very quickly. One of the technologies of this development is the internet. The use of the internet is very helpful in distributing information because it can be accessed anywhere and anytime. However, freedom in using internet access can also be misused and has a negative impact. An example is accessing websites that are dangerous or not suitable to be accessed. Therefore, it is necessary to guarantee the use of the internet that is equipped with a system that can filter negative sites so that they cannot be accessed freely. The solution that can be applied is the use of proxy server technology that can perform access management on the internet. The proxy server will be implemented using the ClearOS operating system ver.7 that has been installed on the server computer. The result of implementing a proxy server based on ClearOS is that it can manage access to sites that should not be accessed by the client computer.